Multiple social media in the workplace: Contradictions and congruencies. (30th August 2017) - Forsgren, Emma; Byström, Katriina
Abstract: In this paper, we report an investigation on the use of multiple social media in knowledge work and explore the contribution of activity theory for such a study. As social media are increasingly adopted at work, there is a demand to understand how they are being incorporated. This study focuses on how social media may improve or reduce coherence in work activities, and for this purpose, we use activity theory as an analytical lens to conceptualise social media usage in a Scandinavian software development company. The qualitative data, consisting of interviews and observations, were analysed to capture the mediating role of social media for information sharing within and across work activities. We found social media in general helpful to maintain coherence in terms of sharing work‐related information, improving ambient awareness, as well as for socialising, but they also caused inconsistencies in use and adoption. In addition, we found that social media served different purposes in different activity systems, causing both contradictions and congruencies; what was seen as a benefit for some work activities appeared as a limitation for others (eg, concerning pace and aims of information sharing). In our findings through the lens of activity theory, we observed how objects, although they were shared, were fractionalised in networked activities. Our conclusion is that despite the still unoptimised functionality, social media do bring coherence in work activities in a decentralised work environment.